2015
DOI: 10.1039/c5ce01049g
|View full text |Cite
|
Sign up to set email alerts
|

Regulated morphology/phase structure and enhanced fluorescence in YF3:Eu3+,Bi3+via a facile method

Abstract: A simple and facile hydrothermal method has been developed to enhance the fluorescence performance of YF 3 : xEu 3+ , y%Bi 3+ (x = 0-0.2, y = 0-1.5) via optimizing the concentration of Eu 3+ and Bi 3+ and regulating the morphology/phase structure by controlling the amount of HNO 3 . The evolutionary mechanism of the micro-topography and microstructure for the samples has been proposed, and the fluorescence and decay properties of the samples have been investigated. It was found that the fluorescence intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 40 publications
1
17
1
Order By: Relevance
“…It can be seen that the variation tendency of decay lifetime of cs‐3 series is not consistent with that of the luminescence intensity. The decay properties of the products are determined by some factors including surface defects, morphology, special junctions of the crystal grains, the number of luminescence centers, and so on . Therefore, this unusual phenomenon is the result of the above factors.…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen that the variation tendency of decay lifetime of cs‐3 series is not consistent with that of the luminescence intensity. The decay properties of the products are determined by some factors including surface defects, morphology, special junctions of the crystal grains, the number of luminescence centers, and so on . Therefore, this unusual phenomenon is the result of the above factors.…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known, for example, that Bi 3+ can act as a sensitizer to enhance lanthanide (Eu 3+ , Tb 3+ , Sm 3+ , and Dy 3+ ) emissions, through Bi 3+ → Ln 3+ energy transfer in different Ln-based hosts. However, very few reports have been devoted to the Bi 3+ → Ln 3+ energy-transfer process in Bi 3+ ,Ln 3+ codoped fluorides. To the best of our knowledge, the only related fluoride system reported is YF 3 :Eu 3+ ,Bi 3+ although the analysis of the Bi 3+ → Eu 3+ energy-transfer process in the material does not seem to be correct because of the clear contamination of the nominally Eu 3+ free sample with Eu 3+ …”
Section: Introductionmentioning
confidence: 95%
“…To the best of our knowledge, the only related fluoride system reported is YF 3 :Eu 3+ ,Bi 3+ although the analysis of the Bi 3+ → Eu 3+ energy-transfer process in the material does not seem to be correct because of the clear contamination of the nominally Eu 3+ free sample with Eu 3+ . 16 On the other hand, because of the high atomic number (Z) of lanthanides (Z = 57−71), Ln:phosphors have additionally been proposed as contrast agents for X-ray computed tomography (CT) in medical diagnosis. 17 Codoping with Bi 3+ is, therefore, not only interesting for the Ln 3+ emission enhancement but also because the high atomic number of Bi (Z = 83) is expected to increase the X-ray attenuation capacity of the material and, consequently, the contrast in the CT image.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] The structure and crystalline phase of YF 3 has been found to have a signicant control over its emissive performance. [24][25][26] So far, several YF 3 nano-and microstructures have been synthesized using a variety of methods to investigate their unprecedented shape-and size-dependent up/down-conversion emission properties. [21][22][23][24][25][26][27][28][29] A majority of the adopted synthetic methods require organic surfactants to control the structure.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] So far, several YF 3 nano-and microstructures have been synthesized using a variety of methods to investigate their unprecedented shape-and size-dependent up/down-conversion emission properties. [21][22][23][24][25][26][27][28][29] A majority of the adopted synthetic methods require organic surfactants to control the structure. Shao et al 30 reported a simple surfactant-free HNO 3 -assisted hydrothermal method to nely tune the structure of YF 3 :Eu 3+ to generate various shapes.…”
Section: Introductionmentioning
confidence: 99%